Appendicitis and COVID: cause or effect? - Raju, Abdus Salam (2023)
Vasculitis and phlebitis with vascular occlusion within appendix specimen is rare. Several authors have reported COVID-19 related veno-occlusive disease in hepatic pathology, but lymphoid aggregation with phlebitis is unusual in appendix specimen. We present a case with medium size venule phlebitis in an appendix of a patient recovered from COVID-19 infection.